Supervisi Akademik Sebagai Upaya Meningkatkan Kompetensi Pedagogik Guru dalam Proses Pembelajaran di SMP Negeri 18 Mataram - H. Lalu Suwarno (Jurnal Paedagogy, 2022)
The purpose of this study is to improve the pedagogic competence of teachers in the learning process in the classroom through the implementation of academic supervision. This research uses the school action research method which is carried out in two cycles, each cycle of which has four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 8 teachers of SMPN 18 Mataram. This research instrument uses observation sheets and documentation. The data analysis technique used descriptive analysis. The results of this study are: 1) the results of principal observations and teacher observations during the mentoring process have obtained an average score of 4.0, 2) the results of the average value of teachers in the learning process reach 85% with an average score of 70 ,00 (good category). The results of the research in the first cycle of principal observations were average (3.80), teacher observations were averaged (3.00) and the results of academic supervision were on average score points (66.12). In cycle II, the average school supervisor's observations (4.40) with the percentage of achievement (100%), the teacher's observations on the average (4.25) with the percentage of achievement (100%) and the results of academic supervision in the target average value (84,92) with the percentage of achievement (100%). The conclusion obtained from the results of this study is that academic supervision can improve the pedagogic competence of teachers in the learning process in the classroom.